Comparison of Contract Theory in Sharia Economic Law and Agreements in the Civil Code - Bayu Saputra; Muhammad Harry Syahputra; Rafa Junita Artati (Media Hukum Indonesia (MHI), 2026)
This study describes the comparison of contract theory in sharia economic law with agreements in the Civil Code as two legal instruments that both function to regulate legal relations between parties, but have different normative bases. This research uses normative legal research methods through a comparative approach to primary, secondary, and tertiary legal sources which include the Civil Code, the Compilation of Sharia Economic Law (KHES), the Qur'an, Hadith, and a number of related legal references. The findings of the study show that agreements in civil law are based on the principles of freedom of contract, consent, and legal certainty, while contracts in sharia economic law not only require the agreement of the parties, but also require obedience to sharia principles in the form of justice, openness, honesty, and prohibition of usury, unclear transactions, and speculation. In addition, the contract contains moral and religious dimensions that are not expressly found in civil agreements. Other differences can be seen in legal resources, binding power, legal objectives, and risk management when the implementation takes place. Based on these results, it can be concluded that harmonization between the Civil Code and KHES is needed to avoid normative clashes while realizing certainty and legal justice in modern economic practices in Indonesia.